THE EFFECT OF JOB CHARACTERISTICS ON JOB SATISFACTION AND ITS IMPACT ON EMPLOYEE PERFORMANCE - aan, sugianto (Advances in Social Sciences Research Journal, 2018)
Research the effect of job characteristics on job satisfaction and its impact on employee performance highlights the influence of job characteristics on job satisfaction and whether it has an influence on employee performance by taking the location of research on cooperatives in Solo, Central Java. Cooperatives face several problems, namely high levels of employee turnover. This study uses quantitative methods using a descriptive approach. For data collection the method used is by giving questionnaires to employees and interviews with informants who then analyzed the data using smart PLS. Based on the results of the study found that job characteristics have a positive but not significant relationship to employee performance, the next job characteristics have a positive and significant relationship to job satisfaction and the last job satisfaction has a positive and significant relationship to employee performance. Keywords: Job Characteristics, Job Satisfaction, Employee Performance